Risk Behaviors in Teens with Chronic Kidney Disease: A Study from the Midwest Pediatric Nephrology Consortium. (4th December 2019) - Xiao, Nianzhou; Stolfi, Adrienne; Malatesta-Muncher, Rossana; Bholah, Reshma; Kogon, Amy; Eddington, Angelica; Chand, Deepa; Greenbaum, Larry A.; Hanevold, Coral; Tran, Cheryl L; Chishti, Aftab; Davis, Keefe; et al.
Abstract : Introduction . There is a paucity of information about risk behaviors in adolescents with chronic kidney disease (CKD). We designed this study to assess the prevalence of risk behaviors among teens with CKD in the United States and to investigate any associations between risk behavior and patient or disease characteristics. Methods . After informed consent, adolescents with CKD completed an anonymous, confidential, electronic web-based questionnaire to measure risk behaviors within five domains: sex, teen driving, alcohol and tobacco consumption, illicit drug use, and depression-related risk behavior. The reference group was composed of age-, gender-, and race-matched US high school students. Results . When compared with controls, teens with CKD showed significantly lower prevalence of risk behaviors, except for similar use of alcohol or illicit substances during sex (22.5% vs. 20.8%, p = 0.71 ), feeling depressed for ≥2 weeks (24.3% vs. 29.1%, p = 0.07 ), and suicide attempt resulting in injury needing medical attention (36.4% vs. 32.5%, p = 0.78 ). Furthermore, the CKD group had low risk perception of cigarettes (28%), alcohol (34%), marijuana (50%), and illicit prescription drug (28%). Use of two or more substances was significantly associated with depression and suicidal attempts (p < 0.05 ) among teens with CKD. Conclusions . Teens with CKD showed significantly lower prevalence of risk behaviors than controls. Certain patient characteristics were associated with increased risk behaviors among the CKD group. These data are somewhat reassuring, but children with CKD still need routine assessment of and counselling about risk behaviors.